Quality and acceptability evaluation of soy-cheese (tofu) enhanced with meat (2023)
The study was carried out to determine the quality and acceptability of soy-cheese (Tofu) enhanced with different meat types. 40g of raw soybeans, 40g of each meat type-beef, mutton, chevon, chicken and 5g of industrial grade calcium sulphate (CaSo4) were used for this study. The meat types + Tofu constituted the treatments, thus: T0 = Tofu only (control), Ti = Tofu + beef, T2 = Tofu + mutton, T3 = Tofu + chevon, T4 = Tofu + chicken meat. Data were collected and analysed using analysis of variance (ANOVA) at p<0.05. The meat Tofu products samples showed significant differences (p<0.05) in physical, chemical and the sensorial variables tested with chicken meat Tofu (T4) having highest (p<0.05) yield, water holding capacity, protein, fat, ash, all the organoleptic and overall acceptability values. This study supplied first hand information on the effect of meat inclusion in Tofu, therefore, chicken meat could be included in Tofu at ratio of 1:1 for quality and acceptability enhancement.